The Call, Sinking Fund, and Term-to-Maturity Features of Corporate Bonds: An Empirical Investigation - Mitchell, Karlyn (Journal of Financial and Quantitative Analysis, 1991)
Karlyn Mitchell, The Call, Sinking Fund, and Term-to-Maturity Features of Corporate Bonds: An Empirical Investigation, The Journal of Financial and Quantitative Analysis, Vol. 26, No. 2 (Jun., 1991), pp. 201-222